Contributions and role of B2 nanoparticles in the exceptional strength/ductility trade-offs of Al0.3CoCrFeMnNi high entropy alloy - Stéphane Gorsse; Dorian Hachet; Stéphane Godet; Rajarshi Barnerjee; Mohamed Gouné (Materials Research Letters)
This study explores the role of B2 nanoprecipitates in enhancing strength/ductility trade-offs in the Al0.3CoCrFeMnNi high-entropy alloy (HEA). A tailored thermomechanical treatment selectively introduced high-density intragranular B2 nanoprecipitates, while an innovative methodology quantified isotropic and kinematic hardening contributions directly from tensile test data, bypassing traditional unloading-reloading cycles. Results highlight the superior kinematic hardening induced by B2 precipitates, surpassing isotropic effects and challenging theoretical models. Increasing the critical tilting strain for isotropic and kinematic components is proposed as a pathway to exceptional mechanical performance, offering a robust framework for optimizing HEAs in advanced alloy design.